A role of atomic size misfit in lattice distortion and solid solution strengthening of TiNbHfTaZr high entropy alloy system. (15th March 2022) - Thirathipviwat, Pramote; Sato, Shigeo; Song, Gian; Bednarcik, Jozef; Nielsch, Kornelius; Jung, Juree; Han, Junhee
Abstract: Systematic variations of chemical compositions in TiNbHfTaZr HEA system were designed for an investigation of compositional complexity and chemical composition effects on lattice distortion. The lattice distortion was quantitatively analyzed by using the pair distribution function (PDF) method. The levels of lattice distortion were proportional to the atomic size misfit rather than the compositional complexity in the TiNbHfTaZr HEA system. The more pronounced lattice distortion in the TiNbHfTaZr HEA system increases the solid solution strengthening. The study suggested that the atomic size misfit is one of the foremost considerations on lattice distortion and solid solution strengthening in the TiNbHfTaZr HEA system. Graphical abstract: Image, graphical abstract